Analysis of anger expression style - Continuous anger and personality types of professional soccer players - Yildiz, M.; Sahan, H.; Tekin, M.; Ulukan, M.; Mehtap, B. (Collegium Antropologicum, 2011)
The purpose of this study was to analyse the anger expression styles, the continuous anger and personality types of players who play football in the professional league. The research group consisted of 133 soccer players who are playing in sports teams in the Turkish Super League: Ankara Sport Club, Gençlerbirliði Sports Club and Hacettepe Sports Club in the first league, Turk Telekom sports in the second league, and Keçiören Gücü Sports and Ankarademir Sports playing in the third league in the 2008-2009 football season. The Eysenck personality inventory was modified to Turkish by Bayar in 19831, having been developed by Eysenck and Eysenck in 19752 and the continuous anger - anger style scale (SOTO) was modified to Turkish by Özer in 19943. The state trait anger scale (STAS) was originally developed by Spielberger in 19834. All these were used on soccer players participating in the study to determine the continuous anger and anger styles in this study. In the interpretation of data, a meaningfulness of p<0.05, was applied by using regression analysis, the Kruskal Wallis Test, the one-way variance analysis (ANOVA) test and the Tukey test to find the differences among the groups. The SPSS (Statistical Package for Social Sciences) programme was used to find the accounted values and to evaluate the data. According to the results of this study, regarding the education level variable, while there was a meaningful difference between the continuous anger sub-dimension and anger control sub-dimension than continuous anger - anger expression styles, no significant difference was found among personality type sub-dimensions (psychoticism, extrovert, neurotic, false). In addition, a significant relationship was found between psychoticism, extrovert, neurotic, and lie sub-dimensions and the personality type sub-dimensions of professional players` constant anger-anger expression styles.